Culture And Women Entrepreneurship: A Case Study Of Nabdam District - Anambane, G. (University of Ghana, 2017)
The purpose of this study was to explore the role of culture in shaping the entrepreneurial behaviour of women. It is believed that the disparities in the levels of entrepreneurship across countries may be caused by differences in culture. However, it appears women entrepreneurship is more responsive to cultural norms and values than male entrepreneurship. In Sub-Saharan Africa especially, most countries have strong cultural practices that traditionally impose restrictions on women and their entrepreneurial behaviour and also create additional barriers for women that make it more difficult for them to start or grow business enterprises. Yet, most existing studies on culture and women entrepreneurship focus on the extent to which national cultural values affect women entrepreneurship by employing quantitative methods, with little probing into “the how”: to give a better understanding of the phenomenon. This study starts to fill this gap by employing a qualitative research approach with the case study design, using face-to-face in-depth interview of 20 women entrepreneurs. The key finding of the study is that culture acts as a ‘push’ motivational factor of women entrepreneurship and largely limit the growth and expansion of women-owned enterprises. This therefore calls for programmes that will stimulate the growth and development of women-owned enterprises, factoring in the predominant cultural issues affecting women entrepreneurs in this area. This study has significant value and it is original since it is the first known study that looks at culture and women entrepreneurship in the Nabdam district (Ghana). The study has unearthed some critical ideas as to how certain cultural practices are shaping entrepreneurial orientation of women in the Nabdam District.
Thesis (MPhil)
Keywords: Culture; Women Entrepreneurship; Nabdam District; Ghana